Macrophage-Associated Lipin-1 Enzymatic Activity Contributes to Modified Low-Density Lipoprotein–Induced Proinflammatory Signaling and Atherosclerosis. Issue 2 (February 2018) - Vozenilek, Aimee E.; Navratil, Aaron R.; Green, Jonette M.; Coleman, David T.; Blackburn, Cassidy M.R.; Finney, Alexandra C.; Pearson, Brenna H.; Chrast, Roman; Finck, Brian N.; Klein, Ronald L.; Orr, A. Wayne; Woolard, Matthew D.
Abstract : Objective—: Macrophage proinflammatory responses induced by modified low-density lipoproteins (modLDL) contribute to atherosclerotic progression. How modLDL causes macrophages to become proinflammatory is still enigmatic. Macrophage foam cell formation induced by modLDL requires glycerolipid synthesis. Lipin-1, a key enzyme in the glycerolipid synthesis pathway, contributes to modLDL-elicited macrophage proinflammatory responses in vitro. The objective of this study was to determine whether macrophage-associated lipin-1 contributes to atherogenesis and to assess its role in modLDL-mediated signaling in macrophages. Approach and Results—: We developed mice lacking lipin-1 in myeloid-derived cells and used adeno-associated viral vector 8 expressing the gain-of-function mutation of mouse proprotein convertase subtilisin/kexin type 9 (adeno-associated viral vector 8-proprotein convertase subtilisin/kexin type 9) to induce hypercholesterolemia and plaque formation. Mice lacking myeloid-associated lipin-1 had reduced atherosclerotic burden compared with control mice despite similar plasma lipid levels. Stimulation of bone marrow–derived macrophages with modLDL activated a persistent protein kinase Cα/βII–extracellular receptor kinase1/2–jun proto-oncogene signaling cascade that contributed to macrophage proinflammatory responses that was dependent on lipin-1 enzymatic activity. Conclusions—: Our data demonstrate that macrophage-associated lipin-1 is atherogenic, likely through persistent activation of a protein kinase Cα/βII–extracellular receptor kinase1/2–jun proto-oncogene signaling cascade that contributes to foam cell proinflammatory responses. Taken together, these results suggest that modLDL-induced foam cell formation and modLDL-induced macrophage proinflammatory responses are not independent consequences of modLDL stimulation but rather are both directly influenced by enhanced lipid synthesis. Abstract : Supplemental Digital Content is available in the text.